PENGARUH WORD OF MOUTH, BRAND IMAGE DAN LIFE STYLE TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT DI PT.HAYATI PRATAMA MANDIRI PADANG - Utami, Lensi Putri; Rahmadanirwati, Dewi (Ensiklopedia of Journal, 2025)
Abstract: Purchasing decisions are the process in which consumers decide to buy a product, which is based on considerations of the needs that must be met. The aim of this research is to determine the influence of word of mouth, brand image and life style on purchasing decisions for Honda Beat motorbikes at PT. Hayati Pratama Mandiri Padang. This type of research is quantitative. This research was conducted at PT. Hayati Pratama Mandiri Padang. The data analysis technique for this research is using SPSS. Determining the sample in the study used probability sampling, namely simple random sampling. The sample for this research was 78 respondents. The results of this research state that Word of Mouth, Brand Image and Life Style have a positive and significant influence on the decision to purchase a Honda Beat motorbike at PT. Hayati Pratama Mandiri Padang.Keywords: Word Of Mouth, Brand Image, Life Style, Purchasing Decisions